THE EFFECTIVENESS OF USING ETHNOMATEMATICS-BASED STUDENT WORKSHEETS (LKS) IN MATHEMATICS LEARNING AT SMPN 1 DENPINA - Yusem Ba'ru; Hakpantria Hakpantria; Egiyanto Poni Bali; Angela Angela (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
One of the ways teachers design a learning environment is to use the right media in teaching a concept so that the concept is easily accepted and understood by students. Therefore, the author offers a solution to use the media or learning resources that exist in the environment of the students in this case ethnomathematics. There has been a lot of research from UKI Toraja that the culture of the Toraja people is rich in ethnomathematics. Therefore the author was inspired to use this in mathematics learning. In this study ethnomathematics will be packaged in student Worksheets. This is considered very appropriate because LKS, which contains instructions for the stages of solving a problem, will challenge students to solve it or find a concept in an interesting way because it uses media in Toraja culture, which is inseparable from the lives of students at SMP 1 Denpina or it can be said that the students are familiar with it. LKS which is based on Ethnomathematics, apart from being a learning medium that helps teachers convey messages to students, the use of ethnomathematics in learning is one way to maintain the local wisdom of the Toraja people so that the younger generation who are currently in the digital era still understand and even maintain the culture they have. This study aims to apply ethnomathematics-based student worksheets in mathematics learning in Schools. The research method used is a quantitative research method. Where in the stages, the author will design student worksheets based on ethnomathematics, then test its validity after it is used in the learning process and during the learning process, student activities will be observed to see the level of student activity during learning using LKS developed by the author. After the learning process is complete, students will be tested using a learning outcomes test. From the results of the study, it was found that the use of ethnomathematics-based LKS in grade VII students of SMPN I was effective, this can be seen from the learning outcomes and activities of the students studied meeting the effective criteria.